Intranasal Administration of Self-Oriented Nanocarriers Based on Therapeutic Exosomes for Synergistic Treatment of Parkinson’s Disease - Peng, Huan; Li, Yan; Ji, Weihong; Zhao, Ruichen; Lu, Zhiguo; Shen, Jie; Wu, Yanyue; Wang, Jianze; Hao, Qiulian; Wang, Jingwen; Wang, Wenli; Yang, Jun; et al. (ACS nano, 2022)
The treatment of Parkinson’s disease (PD) has been hindered by the complex pathologies and multiple membrane barriers during drug delivery. Although exosomes derived from mesenchymal stem cells (MSCs) have great potential for PD, MSC-derived exosomes alone could not fully meet the therapeutic requirements due to their limitation in therapy and delivery. Here, we develop a self-oriented nanocarrier called PR-EXO/PP@Cur that combines therapeutic MSC-derived exosomes with curcumin. PR-EXO/PP@Cur can be self-oriented across the multiple membrane barriers and directly release drugs into the cytoplasm of target cells after intranasal administration. With enhanced accumulation of drugs in the action site, PR-EXO/PP@Cur achieves three-pronged synergistic treatment to deal with the complex pathologies of PD by reducing α-synuclein aggregates, promoting neuron function recovery, and alleviating the neuroinflammation. After treatment with PR-EXO/PP@Cur, the movement and coordination ability of PD model mice are significantly improved. These results show that PR-EXO/PP@Cur has great prospects in treatment of PD or other neurodegenerative diseases.